Mercury bioremoval by Yarrowia strains isolated from sediments of mercury-polluted estuarine water - Oyetibo, Ganiyu Oladunjoye (Appl Microbiol Biotechnol, 2014)
Difference in mercuric ion removal by resting and growing cells of two mercury-resistant yeast strains, identified as Yarrowia spp. (strains Idd1 and Idd2), were studied. Resting cells of strain Idd2 exhibited high maximum Hg(2+) removal capacity (59 mg mercury per g dry cell weight [gdw(−1)]) by adsorption than those of resting cells of strain Idd1 (32 mg gdw(−1)). The resting cells of strain Idd2 exhibited a higher Hg(2+) desorption capacity using CaCl(2) (68 %) and EDTA (48 %) than strain Idd1, depicting weaker binding of Hg(2+) onto strain Idd2 unlike strain Idd1. The actively growing yeast cells showed opposite Hg removal characteristics to those of the resting cells. Strain Idd1 adsorbed less Hg(2+) from culture medium supplemented with Hg(2+) than strain Idd2. However, the growing strain Idd1 reduced and vaporized 27 % of supplemented Hg(2+) as metallic mercury (Hg(0)), while the growing strains Idd2 vaporized 15 % of the supplemented Hg(2+). These two yeast strains are potential biotechnological tools for the eventual bioremediation of polluted aquatic systems. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00253-014-6279-1) contains supplementary material, which is available to authorized users.